A beam to 3D model switch for rotor dynamics applications. (1st February 2015) - Tannous, Mikhael; Cartraud, Patrice; Dureisseix, David; Torkhani, Mohamed
Highlights: Use of a 3 D model and a beam model at two different stages of the same computation. For rotor dynamics problems with non linearities restricted in space and time. The switch reduces considerably the computational cost with preserved accuracy. The energy consistency of the switch is demonstrated. The gyroscopic effects are taken into account. Abstract: A typical accidental slowing down of a turbine presents a rotor–stator contact that may be limited to a small interval of the whole simulation period. Such engineering problems involving slender structures with local or non linear phenomena restricted in time require a 3 D model for a better understanding of the local or non linear phenomena, whereas a simplified beam model can be sufficient for simulating the linear phenomena occurring for a long period of time. This paper proposes a strategy that enables to switch from a beam model to a 3 D model during a transient rotor dynamics analysis, and thus, allows to reduce the computational cost while preserving a good accuracy. The simulation starts with a beam model, and at the switch instant t s, the 3 D solution is initialized as the sum of a displacement corresponding to the classical Timoshenko kinematics assumption and a 3 D correction that accounts, for instance, for cross-section deformation. This is performed on three consecutive time steps (the switch instant, the previous and the following steps), thus allowing to make velocity and acceleration corrections. The method is proved to be energetically sound and is validated through comparisons with a reference solution corresponding to the 3 D model solution computed during all the simulation.